Pattern of Surgical Procedures in Emergency Department of Allama Iqbal Memorial Teaching Hospital Sialkot (Medical Forum Monthly, 2024)
Objective: To study the pattern of surgical procedures in emergency department of Allama Iqbal Memorial Teaching Hospital, Sialkot.Study Design: Descriptive / observational studyPlace and Duration of Study: This study was conducted at the Allama Iqbal Memorial Teaching Hospital, Sialkot from July 2015 to July 2016.Materials and Methods: Nine Hundred and ten surgical procedures were included in this retrospective study. All the surgical procedures were included, while cases that were shifted to other departments and those that left against medical advice were excluded. Age, sex, area, type of surgical procedures, was recorded on the designed Performa. Permission of Ethical Committee of the institute was taken. Data was analyzed on SSPS version 10.Results: In this study the incidence of surgical procedure in emergency department was maximum (42.41%) 386 cases at the age group 15-25 years and minimum (0.21%) 2 cases at the age group 90 & above as shown in table no.01. There were (56.70%) 516 cases from male and (43.29%) 394 cases from female as shown in table no.02. The surgical procedures of the patients from urban population was (65%) 588 cases and (35%) 322 cases from rural populations as shown in table no.03. The incidence of open appendectomy was at the top (11.20%) 102 cases in male and (15.27%) 139 cases from female and there was lowest incidence (0.1%) 1 in case of chest intubation, tendon repair, vascular repair, and exploratory laparotomy for gun shot in female patients as shown in table no.04. There were (10%) 91 cases from male and (9.45%) 86 cases from female of emergency excision of soft issue lesions, (10.10%) 92 cases from male and (8.13%) 74 cases from female in case of incision and drainage procedure. The exploratory laparotomy for typhoid perforation, duodenal ulcer, stab wound and blunt abdominal trauma was the second most common procedure carried out at the surgical emergency department of Allama Iqbal Memorial Teaching Hospital, Sialkot as shown in table no.04.Conclusion: The results of this study are helpful in planning better emergency service delivery to patients and in focusing and improving the training of surgical residents. Government at various levels should provide modern diagnostic tools for the accurate preoperative diagnosis of surgical emergencies in tertiary care public hospitals.